IMPLEMENTASI E-COMMERCE PADA PERANCANGAN MARKETPLACE GURU PRIVATE DENGAN MODEL APPRECIATIVE INQUIRY BERBASIS WEB - ASAZIDUHU GEA (LP2MTBM MAKARIOZ, 2019)
Internet technology has now become an inseparable part of human activity. The rapid use of the internet encourages people to innovate in their various activities to make it very easy to increase revenue on commercial systems. Humans are competing to transfer the methods of data processing and traditional business transaction transactions to a computerized system known as E-commerce. Including the need in the education system encourages all components related to using the internet. One of the needs in the education system is private teachers. For example dance teacher, guitar teacher, and subject teacher. The private teacher search system that is currently still searching uses contacts with colleagues, or recommendations from previous tutors, to broadcast through social media. For this reason, this study discusses the design of the marketplace in ordering private teachers. The results of this research are in the form of private teacher marketplace design using a web-based Appreciative Inquiry model that can be used by customers to use the services of private teachers by knowing the competencies and track-records of prospective private tutors.